Periprocedural Polypharmacy in Lumbar Fusions Performed Under Spinal Anesthesia Compared With General Anesthesia. Issue 3 (24th March 2023) - Olmos, Michelle; Hernandez, Nicholas S.; Kanter, Matthew; Liu, Penny; Riesenburger, Ron I.; Kryzanski, James
Abstract : BACKGROUND: Spinal anesthesia (SA) is a safe and effective alternative to general endotracheal anesthesia (GEA) for lumbar surgery. Foremost among the reasons to avoid GEA is the desire to minimize postoperative cognitive dysfunction (POCD). Although POCD is a complex and multifactorial entity, the risk of its development has been associated with anesthetic modality and perioperative polypharmacy, among others. OBJECTIVE: To determine whether SA reduced polypharmacy compared with GEA in patients undergoing transforaminal lumbar interbody fusion (TLIF). METHODS: Demographic and procedural data of 424 consecutive TLIF patients were extracted retrospectively. Patients undergoing single-level TLIF through GEA (n = 186) or SA (n = 238) were enrolled into our database. Perioperative medications, excluding antibiotic prophylaxis and local anesthetics, were classified into various categories. RESULTS: Patients in the SA cohort received a mean of 4.5 medications vs a mean of 10.5 medications in the GEA cohort ( P < .0001). This reduction in perioperative medications remained significant after a multivariate analysis to control for confounders ( P < .001 for all variables). The use of vasopressors was significantly reduced in the SA cohort ( P < .001), which coincided with a significant reduction in hypotensive episodes ( P < .001). Patients undergoing TLIF through GEA had 3.6 times greater odds of experiencing a hypotensive episode intraoperatively (odds ratio = 3.62, 95% CI [2.38-5.49]). CONCLUSION: Spinal anesthesia is associated with a significant decrease in perioperative medications and may confer superior intraoperative hemodynamic stability, which lowers pressor requirements. The decrease of perioperative medications may be an important contribution in reducing the incidence of POCD in patients undergoing TLIFs, although this requires further study.